The relationship between shoulder and wrist muscle flexibility and hand muscle strength with the smash accuracy in Badminton - Ahmad Ridho Abiwan; Syafaruddin Syafaruddin; Destriana Destriana (Universitas Negeri Malang, 2024)
Background: Smash accuracy in badminton games is often the primary problem athletes face to earn points, so it is necessary to investigate the relationship between smash accuracy with shoulder and wrist muscle flexibility and hand muscle strength. Objective: This study aimed to determine the relationship between shoulder and wrist muscle flexibility and hand muscle strength with smash accuracy in badminton. Methods: This study uses a correlation method to assess the relationship between shoulder and wrist muscle flexibility, hand muscle strength, and badminton smash accuracy. In this study, all male athletes of PB Club. Mandiri Palembang, totaling 30 people with an age range of 13-17 years. The instruments include flexibility tests (static flexibility tests for shoulders and wrists), hand muscle strength assessments (push-ups), and badminton smash accuracy tests. Results: The results of data processing and analysis using simple regression and multiple regression tests obtained the following results: (1) The relationship between shoulder and wrist muscle flexibility and badminton smash ability produces an R-value of 0.435 with a significance of 0.193 (p>0.05). (2) The relationship between hand muscle strength and badminton smash ability produces an R-value of 0.419 with a significance of 0.790 (p <0.05). (3) The relationship between shoulder and wrist muscle flexibility and hand muscle strength with badminton smash accuracy results in an R-value of 0.591 with a significance of 0.737 (p<0.05). Conclusion: The results showed a relationship between shoulder and wrist muscle flexibility and hand muscle strength in badminton smash accuracy. The magnitude of the relationship between shoulder and wrist muscle flexibility and hand muscle strength to the results of badminton smash accuracy is with an R-value of 0.591, which is greater than the r-table 0.374. This means that the better the shoulder and wrist muscle flexibility and hand muscle strength an athlete has, the better the accuracy of the athlete's smash results will be.